The development and validation of a stability indicating RP-UPLC method for the simultaneous estimation of clarithromycin, amoxicillin, and vonoprazan in a physical mixture - Charumathi Salva, Rajitha Galla (Journal of Applied Pharmaceutical Science, 2024)
A novel technique was developed for simultaneous quantification of clarithromycin (CLA) amoxicillin (AMO), and vonoprazan (VON) in a mixture using the reverse phase ultra-performance liquid chromatography (RP-UPLC) technique and validated as per International Council for Harmonization (ICH) guidelines as there was no literature published for its estimation by UPLC. The method was developed using an acquity UPLC system from waters corporation with Hibar Bis phosphonate C18 column (100 × 2.1 mm, 2 μm) at 35°C and tunable ultra-violet detector (TUV) with detection wavelength at 210 nm, has a run time of below 3 minutes. The mobile phase proportion of 60:40 of 0.1 N monobasic potassium phosphate buffer (pH 3.8) and acetonitrile at a flow velocity of 0.2 ml/ minute was utilized. Linearity was observed for CLA, AMO, and VON between the concentration ranges of 25–150, 25–150, and 1–6 μg/ml, respectively, and R2 was 0.999 for CLA, AMO, and VON. Accuracy and precision were within 2% of the coefficient of variation (RSD) for all drugs. The observed mean percentage recoveries for the CLA, AMO, and VON were determined to be 99.74%, 99.07%, and 99.8%, respectively. The stability of the approach was assessed using degradation studies by exposing it to acid, alkali, oxidizing agent, heat, Ultra Violet (UV) light, and water as per ICH guidelines.
Keywords: Novel, RP-UPLC, mixture, vonoprazan, quantification, stability